Pengembangan Pembelajaran Pendidikan Islam Merespon Era Digital Di SMA 1 Teupah Tengah Kabupaten Simeulue - Yusriman Yurisman; Fakhrijal Fakhrijal (Ikhtisar: Jurnal Pengetahuan Islam, 2024)
In the digital era, human work can be done more efficiently by using equipment that has been integrated with digital devices, as is the case in the world of education. Education must adapt to development because it cannot be separated from development. This study applies a descriptive qualitative approach and uses observation, interview and documentation data collection techniques. In the modern era, teachers have to be creative. This includes using various technologies and integrating them in the learning process to increase motivation and make learning more unique and interesting. At SMA 1 Teupah Tengah, Simeulue Regency, Islamic education teachers have been able to adapt to digital technology because every learning process uses digital media.